POTENTIAL AND UTILIZATION OF CORN HARVEST WASTE BASED ON ANIMAL FEED PROCESSING IN TAROANG DISTRICT, JENEPONTO DISTRICT - Hasanuddin; Mustamin, Siti Walidah; Amin, Saifuddin; Reski Adi (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
This service aims to identify the potential and utilization of corn harvest waste as raw material for animal feed in Taroang District, Jeneponto Regency. Corn harvest waste, such as stems, leaves and cobs, is often not utilized optimally and becomes an environmental problem. Through community service carried out by a team from Muhammadiyah University of Makassar, a series of activities were carried out to introduce corn waste processing technology using a chopper. Demonstrations and training on the use of chopping equipment were carried out to increase the community's understanding and skills in processing corn waste into quality animal feed. The results of this activity show that the use of corn waste as animal feed has great potential to increase the economic value of agricultural waste and reduce environmental impacts. Apart from that, the people involved in this program, especially the "Tersayang" farmer group in Baling-Balang Village, received direct benefits in the form of increased knowledge and skills in processing corn waste. It is hoped that the handover of the chopping equipment to this farmer group will support the sustainability of the animal feed processing business in the future. This community service program has not only succeeded in introducing corn waste processing technology, but also opened up new economic opportunities for the people of Taroang District. Thus, the use of corn harvest waste based on animal feed processing can be an effective solution to improve farmers' welfare and preserve the environment.